In Situ Metabolomics Expands the Spectrum of Renal Tumours Positive on Tc-99(m)-sestamibi Single Photon Emission Computed Tomography/Computed Tomography Examination - Papathomas, Thomas; Tzortzakakis, Antonios; Sun, Na; Erlmeier, Franziska; Feuchtinger, Annette; Trpkov, Kiril; Bazarova, Alina; Arvanitis, Alexandros; Wang, Wanzhong; Bozoky, Bela; Kokaraki, Georgia; Axelsson, Rimma; et al. (European Urology Open Science, 2020)
Background: Definite noninvasive characterisation of renal tumours positive on Tc-99m-sestamibi single photon emission computed tomography/computed tomography (SPECT/CT) examination including renal oncocytomas (ROs), hybrid oncocytic chromophobe tumours (HOCTs), and chromophobe renal cell carcinoma (chRCC) is currently not feasible.
CRIS-Team WoS Importer:2021-01-15